2022
DOI: 10.3390/jpm12101724
|View full text |Cite
|
Sign up to set email alerts
|

The Trochlear Groove of a Femoral Component Designed for Kinematic Alignment Is Lateral to the Quadriceps Line of Force and Better Laterally Covers the Anterior Femoral Resection Than a Mechanical Alignment Design

Abstract: Background: A concern about kinematically aligned (KA) total knee arthroplasty (TKA) is that it relies on femoral components designed for mechanical alignment (MAd-FC) that could affect patellar tracking, in part, because of a trochlear groove orientation that is typically 6° from vertical. KA sets the femoral component coincident to the patient’s pre-arthritic distal and posterior femoral joint lines and restores the Q-angle, which varies widely. Relative to KA and the native knee, aligning the femoral compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…However, variations ranging from 3° to 11° have been observed between manufacturers [4]. This has recently led to the design of femoral components specific to personalized alignment that feature a 20.5° capture in the trochlear groove [42]. The present study suggests that the KA approach would result in even more valgus being added to the TA, which would further displace the trochlea and patella from their native positions.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, variations ranging from 3° to 11° have been observed between manufacturers [4]. This has recently led to the design of femoral components specific to personalized alignment that feature a 20.5° capture in the trochlear groove [42]. The present study suggests that the KA approach would result in even more valgus being added to the TA, which would further displace the trochlea and patella from their native positions.…”
Section: Discussionmentioning
confidence: 83%
“…As this understanding has grown, alignment philosophy has also evolved to a more individualized approach [17,29]. However, doing so with standard femoral components that were initially intended for MA has led to the concern that this may be deleterious to the PFJ [26,41,42]. The average femoral component that was designed for MA has a distal trochlear sulcus angle of around 83°-85°, or 5°−7°valgus [2,32].…”
Section: Implications For Implant Design and Placementmentioning
confidence: 99%
“…A second explanation is that four 3‐D analysis studies reported a difference between three femoral component designs positioned with unKA and the native trochlea and concluded that although randomized trials have not shown differences in patellofemoral complications between KA TKA and MA TKA, a femoral component explicitly designed for KA that more closely restores the native trochlear anatomy might improve patient‐reported satisfaction and function [14, 15, 21, 22]. Finally, a study of sequential bilateral unKA TKA with a PTA of 20.5° valgus explicitly designed for KA in one knee and a PTA of 6° valgus in the opposite knee reported that the 20.5° valgus PTA of the KA‐designed femoral component was lateral to the QV in all patients with negligible lateral undercoverage of the anterior femur resection surface [25]. Hence, the present study’s finding that the FJS is 17 points better when the PTA is lateral to the QV suggests that a KA‐designed femoral component with features of a lateralized prosthetic trochlea and a wider PTA that is lateral to the QV in all patients might better ‘funnel’ patella engagement and improve PROMs.…”
Section: Discussionmentioning
confidence: 99%
“…A PTA that deviates lateral relative to the QV (i.e., positive PTA-QV angle) includes the patient's Q-angle, allowing the natural line of force. However, a PTA that deviates medially excludes the patient's Q-angle, causing an unnatural line of force with potential consequences of shifting the patella medially and adversely affecting patellofemoral kinematics and clinical outcome scores [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation